Searching for the Fastest Route to Tourist Attractions with the Kruskal Algorithm in the C++ Programming Language - Roseandree, Billdan Satriana; Mulyana, Amanda Jayanti; Fuji, Raymico; Pratama, Aldini Hegle; Purnama, Purnama (Universitas Pendidikan Indonesia (UPI), 2023)
In the tourism industry, it is important to find the fastest way to various attractions. In this research, the use of efficient and accurate algorithms facilitates the travel planning process. One algorithm that has proven effective in solving this problem is Kruskal's algorithm. The purpose of this research is to implement Kruskal's algorithm in C++ programming language to find the fastest route between tourist destinations. In this research, the C++ programming language is used to implement the Kruskal algorithm. Information about tourist attractions and distances between tourist destinations are presented in a graph. Kruskal's algorithm is used to find the shortest path using the concept of MST (minimum spanning tree). The result of this research is a C++ program that can use Kruskal's algorithm to find the fastest route between tourist destinations based on the shortest distance. The program leads to a number of tourist destinations that must be visited to get the fastest route. Using Kruskal's algorithm, the program successfully finds the fastest route between tourist destinations, considering the shortest distance. Thus, this research provides an efficient and accurate solution to the problem of determining the fastest route in the tourism industry. The resulting program can be a useful guide for tourists when planning their trips and optimizing time and effort to visit various tourist attractions.